Peningkatan Pengetahuan Dan Kreativitas Siswa Kelas VI Dalam Menyusun Pola Lantai - Firmansyah Hanif Miftafurohim; Insanul Qisti Barriyah (PT. ALHAFI BERKAH INDONESIA, 2023)
The motivation behind this research stems from the primary school kids' limited understanding and lack of inventiveness when it comes to arranging floor patterns in dance. The objective of this study is to assess the cognitive abilities and artistic innovation of primary school kids in the arrangement of dance floor patterns, and propose strategies to enhance their proficiency and inventiveness in this domain. The research was carried out at SDN Pleret Lor, including a total of 10 pupils in the sixth grade. The employed research methodology is qualitative research, specifically descriptive study. Data gathering techniques encompass the methods of observation, documentation, interviews, and surveys. The findings of this study indicate that students' proficiency and ingenuity in organising floor designs are frequently deficient. The researchers propose a novel approach, called the MPPM method, to enhance students' knowledge and creativity in creating floor patterns. This strategy involves a sequence of learning activities, starting with reading and watching, followed by guided direction, project work, and evaluations. During the guided briefing stage, students receive instructions on how to organise floor patterns in dance and the factors that need to be taken into account when organising them, such as their compatibility with dance themes, costumes, and motions.